43+5x-8=90

Simple and best practice solution for 43+5x-8=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 43+5x-8=90 equation:


Simplifying
43 + 5x + -8 = 90

Reorder the terms:
43 + -8 + 5x = 90

Combine like terms: 43 + -8 = 35
35 + 5x = 90

Solving
35 + 5x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-35' to each side of the equation.
35 + -35 + 5x = 90 + -35

Combine like terms: 35 + -35 = 0
0 + 5x = 90 + -35
5x = 90 + -35

Combine like terms: 90 + -35 = 55
5x = 55

Divide each side by '5'.
x = 11

Simplifying
x = 11

See similar equations:

| 24x^2-15x-9=0 | | -14r-48=2(r+8) | | 3.5r=245 | | A+8-4=-2 | | 4=22a | | 4x^3-3x-k=0 | | 3n-5=2*n | | 8y+2=2(y+5)-y | | 3v=4v-6 | | w/3=−9 | | -30x^2+13x+10=0 | | 3(f+4)=18 | | 9t-10=7t-6 | | -6(3x+4)=32 | | 2/0.0095 | | 8.63x+16=74.4769+4x | | 4+x+3x=-2(2x+5) | | 5x+4=3x^2 | | -48x^2+36x+12=0 | | 8/4x=26/4 | | -4(4y-4)-y=-2(y-3) | | -8+8b+2b=-18 | | 2b+7=5b+1b | | 2m-3-5=-10 | | 8(1+3x)-1=7(1+8x) | | 0.666666667(p-12)=-(2p-1)+7 | | 56x^2-41x-7=0 | | 0.5t+3.6=42-1.5t | | 9(y+1)=-9 | | -14f+3.8=1.3f-5.8 | | C=39.87x+.25 | | 36=9(x-3) |

Equations solver categories